Nonprofit boards: Size, performance and managerial incentives - Aggarwal, Rajesh K.; Evans, Mark E.; Nanda, Dhananjay (Journal of Accounting and Economics, 2012)
We examine relations between board size, managerial incentives and enterprise performance in nonprofit organizations. We posit that a nonprofit's demand for directors increases in the number of programs it pursues, resulting in a positive association between program diversity and board size. Consequently, we predict that board size is inversely related to managerial pay-performance incentives and positively with overall organization performance. We find empirical evidence consistent with our hypotheses. The number of programs is positively related to board size. Board size is associated negatively with managerial incentives, positively with program spending and fundraising performance, and negatively with commercial revenue, in levels and changes.